Technology adoption of automated vendor management system in Company Z through technology assessment and scenario planning - Bordeos, Eliza R. (University of the Philippines Diliman, 2017)
The study focuses on the Vendor Management System (VMS) of Company Z. Company Z is a utility company serving 6 million people in Metro Manila. The goal of the company is to become a leader in its industry. This comes with support with the national development and environmental sustainability. Vendor management is under the Supply Chain Management (SCM). SCM is responsible in supply of goods and services to support the overall operations of the company. It has four departments namely, Procurement, Logistics, Warehousing and Vendor Management. Procurement department is the team who handles the purchases of the goods and services of the company. Logistics is the one that delivers or mobilizes the goods and services to warehouses and customers. Warehousing generates stock status, monitors delivery, and manages the warehouse of materials of the company. Vendor management is responsible for accreditation, data analytics, monitors vendor performance and risk assessment of vendors that supports the needs of the company.